Ashes Thrown to the Wind: The Elusive Nature of Transgression. (November 2013) - Littlefield, David; Mosley, Jonathan; Sara, Rachel
Abstract Transgression is not absolute. What constitutes a transgression is forever in flux, being redefined with the mores of society. The potential for transgression also does not halt with the completion of a building. David Littlefield examines the temporal character of transgression in relation to lived‐in buildings, and the manner in which transgression lodges itself between a building and an idea. Here transgression is a byproduct of the occupiers rather than their makers, sometimes to the extent that a building can take on unbearably horrific associations.